Efforts To Prevent the Occurrence of Violence Against Children Through Increasing Understanding of The Community - Anis Widyawati; Dian Latifiani; Pratama Herry Herlambang; Heru Setyanto; Roy Priyono; Ardi Sirajudin Ra'uf; Muhammad Zaidan Dhiya' Ulhaq (Universitas Muhammadiyah Malang, 2022)
Violence against children can be defined as an event of a physical, mental, or sexual injury which is generally carried out by people responsible for the child's welfare, all of which are indicated by harm and threats to the health and welfare of the child. Based on Law 35/2014, violence against children is an act against a child that results in physical, psychological, or sexual misery or suffering and/or neglect, including threats to commit acts, coercion, or deprivation of liberty in an unlawful manner. Children are not only victims of violence but can also become perpetrators of violence after experiencing the same treatment. Therefore, efforts have been made to prevent violence against children through increasing understanding and assistance to the community of Puguh Village, Boja District, and Kendal Regency. The output target of this service is the publication of articles in the IJCLS Sinta S4 journal and news publications in print/electronic mass media as well as video highlights that contain this service activity. The methods used to solve the problem of this service program are: (1) partner needs survey, (2) socialization, and (3) Evaluation. The implementation of this service program is planned for a period of 8 (eight) months, with the following stages: (1) Analysis of partner problems; (2) the need for science and technology for the community; (3) Coordination with partners; (4) socialization; (5) evaluation. The target audience for this service program is the general public who are not yet optimal in understanding violence related to children at school, at home, and in the wider community. Upaya Preventif Terjadinya Kekerasan Terhadap Anak Melalui Peningkatan Pemahaman Masyarakat Desa Puguh Kecamatan Boja Kabupaten Kendal Kekerasan terhadap anak dapat didefinisikan sebagai peristiwa perlukaan fisik, mental, atau seksual yang umumnya dilakukan oleh orang-orang yang memiliki tanggung jawab terhadap kesejahteraan anak, yang mana itu semua diindikasikan dengan kerugian dan ancaman terhadap kesehatan dan kesejahteraan anak. Berdasarkan UU 35/2014, kekerasan terhadap anak adalah setiap perbuatan terhadap anak yang berakibat timbulnya kesengsaraan atau penderitaan secara fisik, psikis, seksual, dan/atau penelantaran, termasuk ancaman untuk melakukan perbuatan, pemaksaan, atau perampasan kemerdekaan dengan cara melawan hukum. Anak-anak tidak hanya menjadi korban kekerasan, tetapi mereka juga bisa menjadi pelaku kekerasan setelah sebelumnya mengalami perlakuan yang sama. Oleh karena itu telah dilakukan upaya preventif kekerasan terhadap anak melalui peningkatan pemahaman dan pendampingan terhadap masyarakat Desa Puguh Kecamatan Boja Kabupaten Kendal. Target luaran pengabdian ini berupa publikasi artikel dijurnal IJCLS Sinta S4 dan publikasi berita pada media massa cetak/elektronik serta video highlight yang memuat tentang kegiatan pengabdian ini. Metode yang digunakan untuk menyelesaikan masalah program pengabdian ini adalah: (1) survey kebutuhan mitra, (2) sosialisasi; dan (3) Evaluasi. Pelaksanaan program pengabdian ini direncanakan dalam jangka waktu 8 (delapan) bulan, dengan tahapan: (1) Analisis permasalahan mitra; (2) Kebutuhan ipteks bagi masyarakat; (3) Koordinasi dengan mitra; (4) sosialisasi; (5) evaluasi. Khalayak sasaran program pengabdian ini merupakan masyarakat umum yang belum optimal dalam memahami terkait kekerasan terhadap anak di sekolah, rumah maupun dimasyarakat luas.